Processo seletivo de alunos do cursinho vitoriano: digitalização e desenvolvimento - Almeida, Larissa Rocha [UNESP]; Araújo, Robson Ricardo; Silva, Aline Gomes [UNESP]; D'Água, Solange Vera Nunes de Lima [UNESP]; Perinelli Neto, Humberto [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Cursinho Vitoriano is an extension program of Sao Paulo State University – UNESP focused on complement the subjects that compose the “vestibular” test, a Brazilian test for students to have access to a high education system. The project has articulated the triad education, research and extension: undergraduation and graduation students can teach, it produces researchs and results on “School Management” and technologies field, and simultaneously it provides free education to community. The project is composed by a group of volunteers that contributes to the development of Cursinho in a pedagogical domain and in the school management field. The latter case, they contribute to the creation of digital tools for the application process to receive new students. This tool has helped the process by storing all the applicants data and has made it faster by spreading the result of the application process in less than one day. Moreover, the storage of the data bank has an important statistics relevance and it adds to an improvement of actions.

O Cursinho Vitoriano é um projeto de extensão da UNESP, voltado para a complementação do ensino, de forma a preparar os alunos para as provas vestibulares. O projeto tem articulado a tríade ensino, pesquisa e extensão, pois atua no ensino, propiciando a alunos de graduação e pósgraduação a prática da docência, produz pesquisas concomitantemente nas áreas de gestão escolar e tecnologias e, caracteriza-se sobretudo como ação extensionista, já que, leva o ensino à comunidade. O Cursinho conta com um quadro de alunosprofessores e colaboradores voluntariados que contribuíram ou contribuem para o desenvolvimento do projeto, tanto para sua qualificação pedagógica, quanto para sua gestão, nesse caso, por meio da criação de ferramentas de digitalização do processo seletivo para novos alunos, fato este que propiciou facilidade ao acesso de dados dos candidatos e agilidade na divulgação do resultado do processo seletivo. Além de servir como importante banco de dados que possuem grande relevância estatística e também contribuem para o aprimoramento de ações.
Keywords: Extension program; Application process; Digitalization; Projeto de extensão; Processo seletivo; Digitalização